3D printing of fillable individual thyroid replicas based on nuclear medicine DICOM data used as phantoms for gamma probe calibration - Kühnel, Christian; Seifert, Philipp; Mulik, Christina; Winkens, Thomas; Freesmeyer, Martin (Nuklearmedizin - NuclearMedicine, 2020)
Aim To proof the feasibility of manufacturing patient-indivdual (anthropomorphic) thyroid replicas from I-124 PET DICOM datasets by means of 3D printing. A possible field of application is the use of those phantoms for the calibration of gamma probes.Methods After editing of the DICOM datasets using several software types and transferring into a dedicated stereolithography format, 10 fillable thyroid replicas (35–200 mL) made of polylactide acid were manufactured via 3D printing. All replicas were filled with a water-solution containing 3.5 MBq I-131 and applied to a standard neck phantom. Calibration factor measurements were carried out using a clinical gamma probe. Measurements were performed with three different tilts: + 15°, 0° and –15°. The influence of the replicas’ volume and the tilt was investigated.Results Manufacturing of the replicas was successful in all cases. The time required for data processing was 13 ± 2 (median: 12, range: 9–25) min and 4–11 h for 3D printing (size-dependent). The printing process could be done overnight. Measured mean calibration factor for straight gamma probe positioning (0° tilt) was 31 965 ± 3360 (33 893, 25 470–34 253) cpm/MBq. A tilt of –15° resulted in lower calibration factors (–7.7 %), whereas a tilt of + 15° led to higher values (+ 9.5 %); p = 0.001. The calibration factors were highly inversely proportional correlated to the volume of the replicas (r = –0.91, p < 0.001).Conclusion 3D printing of patient-individual (anthropomorphic) fillable thyroid replicas was feasable for a large range of volumes. The study demonstrates the influence of the volume as well as the tilt of the measured object for calibration factor measurements with gamma probes.
Keywords: thyroid; phantom; replica; 3D print; uptake measurement